1987
DOI: 10.1007/bf00116168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring immigrant students' adjustment to learning in their new cultural setting

Abstract: The adjustment of non-English speaking immigrant students to learning was explored by comparing the learning characteristics of immigrant students with those of a matched group of Canadian students. Eleven immigrant students and eleven Canadian students from three grade 4 classrooms in three schools in a large Western Canadian urban school system were assessed on academic achievement, attitude to school, English proficiency, academic serf-concept, and quality of teacher-student interaction. Data on attitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Galton, Morrison and Pell (2000), for instance, concluded that the child's age and stage of development at the time of transfer are important factors in determining its impact, while Anderson, Jacobs, Schramm and Splittgerber (2000, p. 33) argued that 'the less prepared students are for systemic transitions, the greater the support they need in making them'. Reasons for failure of Grade 4 immigrants to integrate into Canadian society, according to Jamieson and Stewin (1987), included not finding the right way to express an idea, lack of comprehension of classroom set-up and not feeling accepted by or having friends, as well as teachers failing to recognise each student's unique background. Karagiannopoulou (1999), meanwhile, emphasised changing school as a major factor in a child's life and suggested that this leads to a sense of bereavement for the environment left behind: 'any transition and change can result in a period of reduced control where mastery of the psychosocial environment is reduced' (p. 28).…”
Section: The Theoretical Context: Children In Transitionmentioning
confidence: 98%
“…Galton, Morrison and Pell (2000), for instance, concluded that the child's age and stage of development at the time of transfer are important factors in determining its impact, while Anderson, Jacobs, Schramm and Splittgerber (2000, p. 33) argued that 'the less prepared students are for systemic transitions, the greater the support they need in making them'. Reasons for failure of Grade 4 immigrants to integrate into Canadian society, according to Jamieson and Stewin (1987), included not finding the right way to express an idea, lack of comprehension of classroom set-up and not feeling accepted by or having friends, as well as teachers failing to recognise each student's unique background. Karagiannopoulou (1999), meanwhile, emphasised changing school as a major factor in a child's life and suggested that this leads to a sense of bereavement for the environment left behind: 'any transition and change can result in a period of reduced control where mastery of the psychosocial environment is reduced' (p. 28).…”
Section: The Theoretical Context: Children In Transitionmentioning
confidence: 98%